1994
DOI: 10.1183/09031936.94.07122205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined inspiratory muscle and cycle ergometer training on exercise performance in patients with COPD

Abstract: E Ef ff fe ec ct ts s o of f c co om mb bi in ne ed d i in ns sp pi ir ra at to or ry y m mu us sc cl le e a an nd d c cy yc cl le e e er rg go om me et te er r t tr ra ai in ni in ng g o on n e ex xe er rc ci is se e p pe er rf fo or rm ma an nc ce e i in n p pa at ti ie en nt ts s w wi it th h C CO OP PD D To determine whether inspiratory muscle training could intensify the known beneficial effects of cycle ergometer training on exercise performance in these patients, we compared the effect of an 8 week insp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
2
5

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 17 publications
6
80
2
5
Order By: Relevance
“…Such reductions, when of 1 point or more, are considered clinically important differences. 8 Sustained maximum inspiratory pressure Such results are consistent with previous studies, which showed that inspiratory muscle training increases abdominal mobility 10 and significantly decreases dyspnea, 30,31,34 which is paramount in patients with COPD in pulmonary rehabilitation programs.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Such reductions, when of 1 point or more, are considered clinically important differences. 8 Sustained maximum inspiratory pressure Such results are consistent with previous studies, which showed that inspiratory muscle training increases abdominal mobility 10 and significantly decreases dyspnea, 30,31,34 which is paramount in patients with COPD in pulmonary rehabilitation programs.…”
Section: Discussionsupporting
confidence: 81%
“…There are also studies that show that by adding inspiratory muscle training to general physical training, an increase in submaximal exercise capacity can be achieved, with clinically important improvement in relation to general physical training. 32,34 In our study, there was no difference between those subjects with and without respiratory muscle weakness for both interventions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Improvements in exercise capacity with IRT alone were generally smaller than with exercise conditioning and IRT combined [4,5]. In this issue of the European Respiratory Journal, the study by WANKE et al [19] supports this finding. They observed that inspiratory muscle training additional to general exercise conditioning, resulted in a 24% increase in maximal work load on the cycle ergonometer, whereas in the general exercise condition alone group only a 12% increase was found.…”
Section: In Ns Sp Pi Ir Ra At To or Ry Y Msupporting
confidence: 80%
“…Recently, PARDY and ROCHESTER [20] demonstrated, in a literature review, a close relationship between training intensity and percentage improvement in PImax. The data of the present study by WANKE et al [19] fall within this relationship as they found a 40% increase in PImax with high imposed pressures (70% and 100% PImax). On the other hand, lower training intensities (30% PImax) in the study of LISBOA et al [5] resulted in a 34% increase in PImax.…”
Section: In Ns Sp Pi Ir Ra At To or Ry Y Msupporting
confidence: 66%